Introduction to soft-set theoretic solution of project selection problem. Issue 7 (3rd October 2016) - Bakshi, Tuli; Sinharay, Arindam; Sarkar, Bijan; Sanyal, Subir Kumar
Abstract : Purpose: The purpose of this paper is to introduce a model of decision-making problem in multi-criteria optimization domain for project selection. The model is built by combining the soft set theory and analytic hierarchical model under fuzziness. Soft set model gives us the opportunity to use parameterization properties. Here, the authors have proved that multiple alternatives can be reduced to make the selection process computationally efficient. Here, the authors illustrate the hybrid method by means of an application of the new mathematical model of soft set theory. Design/methodology/approach: This paper is designed to excel a decision support system with multiple criteria analysis tool, analytic hierarchy process combined with soft set theory under fuzziness. Findings: In this paper, the authors have taken four projects P1, P2, P3 and P4 . As per chosen parameters of softest theory the result of the illustrative example reveals that P2 is the best project. The ranking the authors get is in the order of P2, P3, P4 and P1 . The algorithm leads the authors to maximize the proper choice in the environment of imprecise information. The main advantage of this method compare to others is that this hybrid method is very simple in terms of calculation and the computational complexity of the proposed algorithm is low. Originality/value: This proposed decision support strategy for an intended project manager helped to take decision in the perspective environment.